Day case locked anterior plating for distal radial fractures is safe with uninterrupted antithrombotic therapy. (February 2021) - Morris, James A.; Little, Max; Ashdown, Thomas; Clough, Oliver T.; Packer, Timothy; Anakwe, Raymond E.
We undertook a matched prospective cohort study over a 4-year period to examine the safety of continuing the administration of regular antithrombotic treatment with warfarin, clopidogrel or aspirin during day case surgical fixation of distal radial fractures. One hundred and one patients were identified and consented to participate in this study. There was only one reported complication: a superficial wound infection treated with antibiotics. No episodes of excessive bleeding were noted intraoperatively. All patients were discharged home on the day of surgery and there were no episodes of readmission, significant bleeding, haematoma requiring intervention, compartment syndrome or wound dehiscence. Complication rates were comparable with those of the matched cohort of patients undergoing the same procedure but who were not taking antithrombotic medications. Level of evidence: IV